Income Inequality Analysis in Sumatra (Case Study of South Sumatera, North Sumatera, West Sumatera Province) - Siboro, Roican; Azansyah, Azansyah (Indonesian Journal of Banking and Financial Technology, 2024)
One indicator of an area of high economic growth is a low level of income inequality. This study aims to determine the development of income inequality that occurs in the provinces of South Sumatra, West Sumatra and North Sumatra, as well as classify and analyze the province based on economic growth and income inequality. The Data used in this study is time series and cross section data with a six-year observation period of 2018-2023 with 3 provinces in Sumatra yajni South Sumatra, West Sumatra and North Sumatra. The methods of analysis used in this study are Wiliamson index analysis, Theil Entropy index analysis, and Klassen typology analysis. With the results of the study, the average level of income inequality in 2018-2023 is in the range of 0.30 to 0.59. The highest income inequality is in the province of South Sumatra 0.59 and North Sumatra 0.45. Inequality in West Sumatra province is at 0.30 then it is categorized as moderate inequality. From Klassen's typological analysis, using the average Wiliamson index in 2018 to 2023, South Sumatra is in Quadrant II which is a fast-growing region, West Sumatra and North Sumatra are in Quadrant IV of the relatively underdeveloped region. From the results of Klassen typology analysis in 2018-2023 regencies or cities in West Sumatra province are in Quadrant II and Quadrant IV, regencies/cities in North Sumatra are in Quadrant I, quadrant II and quadrant IV. While the district / city in South Sumatra province located in Quadrant II and Quadrant IV.